O direito à acessibilidade no ensino superior privado como medida assecuratória da efetividade do princípio da igualdade: garantias legais e distinção entre promoção e facilitação - Barros, Roberta Lins Estevam de (2021)
Recently, the fundamental right to accessibility has been subjecting to innumerable debates, doubtlessly had to the legal innovations introduced by the Brazilian Law of Inclusion of the person with a disability, that require changes in the legal system, economy, environmental and social spheres, among others, imposing the needs of transformation of the behaviour of human being. This dissertation search to understand the basic principles and the right to accessibility, its historical evolution, its concepts, from the regulatory landmark of Brazilian higher education and its impacts for the access and promotion; doctrinal and legislative studies involving the basic guarantees, much beyond the Federal Constitution of 1988, to also accumulate of stocks the infra-constitutional study of laws, international administrative and treated norms, taking in consideration the requisite taxes to the private institutions of higher education. All of this is in searching to point the needs of if considering the right to the accessibility in assuring the private higher education as measured of the effectiveness of the beginning of the equality, bringing to baila studies on the legal guarantees and pointing distinction between promotion and facilitation of the access and the permanence in private higher education. The interest for the subject of the analysis reiterated in the professional environment of problems related to accessibility is justified ahead. Regarding the used methodology, is about qualitative research, who's given raised they more supply to details and depth of knowledge (the example of the doctrine and the jurisprudence) the improved agreement of the disclosed implications. The focus of the dissertation is on the subjective character of the object, in the study of its particularities and individual experiences. The quarrel process is the dialectic; therefore, it analyses definitive reality, collating theses and antitheses, searching the synthesis, aiming to contribute with the improvement of the process in the area of the education of people with disabilities. Finally, the study counts on the bibliographical technique, applied in such a way employing how much indirect the direct analysis of the workmanships of doctrinaires, research to the workmanships of dedicated national and international researchers to the subject and the studies correlates